(untitled) (Bangladesh Journal of Medicine, 2023)
Background: Neutrophil to lymphocyte ratio calculated from white cell differential count provides a rapid indication of the extent of an inflammatory process. The aim of the study was to evaluate the predictive value of neutrophil to lymphocyte ratio and SOFA score in sepsis outcome. Methods: Adult patients presenting to medicine department of CMCH with suspected sepsis by qSOFA score were considered for the present study. Baseline qSOFA, SOFA Score and NLR were calculated. Patients were followed until discharge or death to observe outcome. The primary outcome was in-hospital mortality. Secondary outcomes were ICU referral and ICU stay. All data were prospectively collected, coded and tabulated. ROC curves were constructed to evaluate the performance of NLR and SOFA in differentiating non-survivors from survivors. Multivariate logistic regression analysis was done to determine the independent predictors adjusted for the previously specified baseline covariates. Results: The AUC for each indicator was compared. NLR had a modest power for predicting unfavorable outcome (death) as suggested by AUC of 0.705 (95% CI: .556-.854), which was greater than that of baseline qSOFA score (0.694). NLR ≥ 8.9 was proposed as the optimal cutoff value, which provided a sensitivity of 75.0% and a specificity of 67.7% for predicting mortality in sepsis. After adjusting for other variables NLR and SOFA remain as independent predictors of unfavorable outcome. Baseline NLR also had a modest power for predicting need for ICU referral than that of baseline SOFA score. Conclusion: NLR is an easily calculated, simple, cost-effective index that could be used as a prognostic tool for clinicians when assessing sepsis patients in the emergency department and general ward. Bangladesh J Medicine 2023; 34(2): 86-92